High-alcohol-content flavored alcoholic beverages (supersized alcopops) should be reclassified to reduce public health hazard. (4th July 2018) - Rossheim, Matthew E.; Thombs, Dennis L.; Treffers, Ryan D.
ABSTRACT: In the US, underage drinkers often consume supersized alcopop – a high-alcohol-content, ready-to-drink flavored alcoholic beverage that is currently regulated as beer. However, calculations in this paper illustrate how the high alcohol by volume and low price of supersized alcopops suggest that they rely on a larger proportion of additives for their alcohol content than permitted to meet the legal definition for beer. From a public safety perspective, it is urgently important that the Alcohol and Tobacco Tax and Trade Bureau assess the formulation of supersized alcopops – specifically, the percent of alcohol in the finished product that is derived from additives. Appropriate reclassification of supersized alcopops as distilled spirits would reduce youth access by resulting in increased price and reduced availability at the retail locations where youth most often obtain alcohol.